CLINICAL MANIFESTATIONS AND CD4 COUNT CHARACTERISTICS OF PATIENTS WITH CYTOMEGALOVIRUS (CMV) RETINITIS - Yunneke Renna Xaverina; Ovi Sofia (International Journal of Retina, 2022)
Introduction: To describe the clinical manifestations and CD4 count characteristics of patients with cytomegalovirus (CMV) retinitis. Methods: This is a retrospective study of patients diagnosed with CMV retinitis at the Ophthalmology Outpatient Clinic at Dr. Saiful Anwar General Hospital, Malang, between January 2016 to December 2019. The patients’ characteristics and clinical data including gender, age, visual acuity, slit lamp biomicroscopy, indirect ophthalmoscope, and laboratory findings were collected from medical records. Result: Twenty-one eyes from thirteen patients with CMV retinitis were enrolled. The mean age was 30.9 ± 7.12 years, with 54% of them male. Bilateral lesions were observed in 62% of the patients, and the mean visual acuity during the initial visit was 1.50 ±1.07 log MAR. All patients presented with the classic form of CMV retinitis. Mean CD4 count when commencing treatment was 62.23 ±11.82 cells/µL with 77% below 50 cells/µL. Patients with CD4 count < 50 cells/µL mostly presented with posterior uveitis, bilateral lesion, and visual acuity ≤1.00 logMAR. Ten patients were given oral valganciclovir and antiretroviral therapy. Retinal detachment condition was noted at seven eyes. Candidiasis was the most presenting opportunistic infection. Conclusion: Cytomegalovirus retinitis was found in patients infected with AIDS with low CD4 counts. In this study, patients with CD4 counts of below 50 cells/µL tend to have more severe clinical presentations.